RESIDIVIS ANAK DI LPKA KELAS I MEDAN: STUDI KASUS MENGENAI FAKTOR DAN SOLUSI TERBAIK - Dharman, Iqbal Rasyid; Wibowo, Padmono (Universitas Nusa Cendana, 2024)
This research discusses the triggering factors leading children to become re-offenders after returning to their families and the community. LPKA has a role in providing proper guidance and education for the future of children. However, in reality, there are still many children at LPKA Kelas I Medan who continue to commit repeated offenses. This research aims to analyze various causes and find the best solutions using the theory of social control. The research was conducted at LPKA Kelas I Medan using a qualitative research method, and the data collection technique involved interviews with re-offending children and their parents. The results of the research show that the social control theory, which includes attachment, commitment, involvement, and individual norms/values, has a significant impact on the rate of child re-offending at LPKA Kelas I Medan when combined with adequate implementation, guidance, quality education, and constructive counseling. Keywords: Correctional Institutions, Recidivist, LPKA